SLEEP PROFILES AND THEIR ASSOCIATIONS WITH COGNITIVE DEVELOPMENT IN CHILDREN WITH - ATTENTION DEFICIT HYPERACTIVITY DISORDER (CIPEEX, 2022)
THE ANALYSIS RECAPITULATES THE IMPORTANCE OF OBSERVING SLEEP DISORDERS IN CHILDREN WITH ATTENTION DEFICIT HYPERACTIVITY DISORDER AND THE DAMAGE CAUSED TO THE NEUROLOGICAL DEVELOPMENT AND DAILY LIFE OF THESE CHILDREN, ALREADY SO AFFECTED BY THEIR PHYSIOLOGICAL DISORDER. THIS INTEGRATIVE LITERATURE REVIEW ADDRESSES ATTENTION DEFICIT HYPERACTIVITY DISORDER (ADHD), WHOSE PATHOGENESIS IS MULTIFACTORIAL AND PRESENTS THE TRIAD OF SYMPTOMS: HYPERACTIVITY, INATTENTION AND IMPULSIVITY. A FREQUENT COMPLAINT IN THIS POPULATION, SLEEP DISORDERS, MAY BE INDICATIVE OF PROBLEMS IN CIRCADIAN RHYTHMS AND RESULT IN BEHAVIORAL, COGNITIVE AND MOOD PROBLEMS. IN ORDER TO CONTRIBUTE TO THE KNOWLEDGE OF THE BIOLOGICAL BASES AND CLINICAL CHARACTERISTICS OF ADHD, THE OBJECTIVE OF THIS REVIEW WAS TO INVESTIGATE POSSIBLE CORRELATIONS BETWEEN BEHAVIOR, ACTIVITY/REST, SLEEP/WAKE RHYTHM PARAMETERS AND THE PRESENCE OF SLEEP DISORDERS IN CHILDREN WITH ADHD. BEHAVIORAL DATA WERE EVALUATED THROUGH THE ANALYSIS OF ARTICLES RELATED TO THE TOPIC IN QUESTION. THE RESULTS SHOWED THAT THERE IS A CLEAR CORRELATION BETWEEN SLEEP DISORDERS AND IMPAIRED COGNITIVE DEVELOPMENT IN CHILDREN WITH ADHD.
Keywords: sleep quality; attention deficit hyperactivity disorder; sleep alterations; children; cognitive development